Fright night - Holland, Tom, 1943-; Jaffe, Herb, 1921-1991.; Sarandon, Chris; Ragsdale, William, 1961-; Bearse, Amanda; McDowell, Roddy; Columbia Pictures; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Columbia Pictures : Sony Pictures Home Entertainment, 2006)
When a teen-age boy can't get anybody to believe that his neighbor is a vampire, he turns to a TV-horror host, who used to be the "Great Vampire Killer" of the movies.
Originally released as motion picture in 1985.
Music by Brad Fiedel.
Chris Sarandon, Roddy McDowall, Amanda Bearse, William Ragsdale, Stephen Geoffreys.
Rated R.
DVD, widescreen (2.35:1) presentation; Dolby surround.
In English and French ; subtitles in English and French.
Keywords: Vampires -- Drama; Television personalities -- Drama; Teenage boys -- Drama; Feature films; Vampire films; Horror films; Video recordings for the hearing impaired